Avaliação das previsões do atraso zenital troposférico para a América do Sul, obtidas usando modelo de previsão numérica de tempo com alta resolução espacial - Sapucci, Luiz Fernando; Galera Monico, Joao Francisco [UNESP]; Toledo Machado, Luiz Augusto; Dos Santos Rosa, Guilherme Poleszuk [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2008)
A Center for Weather Forecast and Climatic Studies of National Institute for Space Research (CPTEC/INPE) has provided to the Brazilian Geodetic community, since 2004, an alternative to correct the GNSS observables from the tropospheric refraction. Numerical Weather Prediction (NWP) Model is used to generate Zenital Tropospheric Delay (ZTD). For the version 1, it was developed a model with horizontal resolution of 100 km, which was updated with Eta model, with resolution of 20 km. This paper provides the most significative details of the current version, as well an evaluation of its quality, using for such ZTD estimates from GPS data collect at RBMC. Comparing to the old version, considerable improvement could be observed from the new model, mainly in Brasilia and Curitiba, reaching up to 55% improvement. When all stations were used in the quality control, almost null bias and RMS of about 4 to 5 cm could be observed.
Evaluation of zenithal tropospheric delay predictions for South America from high spatial resolution numerical weather prediction model
Keywords: Tropospheric modeling; Zenithal Tropospheric Delay; ZTD; Numerical Weather Prediction